2020
DOI: 10.1038/s41467-020-17744-x
|View full text |Cite
|
Sign up to set email alerts
|

Creation of acoustic vortex knots

Abstract: Knots and links have been conjectured to play a fundamental role in a wide range of scientific fields. Recently, tying isolated vortex knots in the complex optical field has been realized. However, how to construct the acoustic vortex knot is still an unknown problem. Here we propose theoretically and demonstrate experimentally the creation of acoustic vortex knots using metamaterials, with decoupled modulation of transmitted phase and amplitude. Based on the numerical simulation, we find that the knot functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 51 publications
0
38
0
Order By: Relevance
“…However, such high-energy ILX states are expected to have small oscillator strengths relative to the lowenergy ILXs. Thus, the increased oscillator strength and the reduced dipole moment can be attributed to a mixing of such high-energy states with the MoSe 2 A exciton A Mo , in the fashion of hybridized inter/intralayer exci-tons recently reported in some bilayer systems (17,18). As a result of this inter/intralayer exciton mixing, R F detects several features in the intralayer exciton range (11).…”
mentioning
confidence: 77%
“…However, such high-energy ILX states are expected to have small oscillator strengths relative to the lowenergy ILXs. Thus, the increased oscillator strength and the reduced dipole moment can be attributed to a mixing of such high-energy states with the MoSe 2 A exciton A Mo , in the fashion of hybridized inter/intralayer exci-tons recently reported in some bilayer systems (17,18). As a result of this inter/intralayer exciton mixing, R F detects several features in the intralayer exciton range (11).…”
mentioning
confidence: 77%
“…At present, various metallic and dielectric metasurfaces have been designed to implement multifunctional planar optical devices, such as metalens [ 14 , 15 ], vortex beam converter [ 16 ] and polarization conversion devices [ 17 , 18 ]. Some subtle metasurfaces have been proposed to construct nanoscale topological light fields [ 19 , 20 ], and a metasurface that consists of rectangular gold nanorods was proposed to realize holographic reconstruction of vortex knots and links [ 21 , 22 ]. Guo et al proposed and experimentally demonstrated a full-dielectric metasurface that can construct vortex knots and links at the nanoscale.…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have witnessed the great development of acoustic vortex beams owing to their extensive applications in a wide range of fields, such as sound communication [1,2] and particle trapping [3][4][5]. The acoustic vortex beam can transfer different-order vortex wavefronts with orbital angular momentum, opening up a new degree of freedom for sound modulations [6][7][8][9][10]. Traditionally, by designing active sound arrays composed of phased sources [2,[11][12][13], researchers have experimentally realized acoustic vortex beams to manipulate micro-particles underwater.…”
Section: Introductionmentioning
confidence: 99%